Outcomes of Children Presenting with Button Battery in Esophagus: A Retrospective Review - Gyawali, Bigyan R; Sharma Guragain, Rajendra P; Neupane, Yogesh; Dutta, Heempali; Shrestha, Lava; Pradhananga, Rabindra B (Journal of Institute of Medicine Nepal, 2020)
Introduction Foreign body in esophagus is a common ENT emergency. Button batteries tend to have more grievous outcomes due to caustic mucosal injury to the esophagus. The objective of our study was to review the clinical profile and outcomes of the paediatric population in our center who presented with button battery in esophagus following accidental ingestion. Methods This was a retrospective study conducted in Tribhuvan University Teaching Hospital, Kathmandu, Nepal. Hospital records of all the patients who presented with button battery esophagus and underwent rigid oesophagoscopic removal from January 2013 to January 2019 were reviewed and analyzed for patient demographics, time interval between ingestion and presentation, site of impaction, status of oesophageal mucosa at the time of rigid oesophagoscopic removal of the battery, early post-operative complications, outcomes at the time of discharge and on follow-up. Results Our final sample size was 11 and all cases were <15 years. The average duration from time of ingestion to presentation to our hospital ranged from 1 day to 2 months. Variable oesophageal mucosal findings such as superficial mucosal erosion, superficial ulcer with slough and granulations with deep discrete ulcer were seen at the site of impaction of the button battery. One case was diagnosed with bilateral abductor palsy on 10th post-operative day following rigid oesophagoscopic removal of the battery. All other cases didn’t develop any significant complications. Conclusion Button battery in esophagus results in oesophageal ulceration and thus warrants an early endoscopic removal. Delayed removal can also cause bilateral abductor palsy from the caustic damage to recurrent laryngeal nerve.